The Strength of Alliance in Individual Psychotherapy and Patient's Wellbeing: The Relationships of the Therapeutic Alliance to Psychological Wellbeing, Satisfaction With Life, and Flourishing in Adult Patients Attending Individual Psychotherapy - Prusiński, Tomasz (Frontiers in Psychiatry, 2022)
Objectives. The central aim of the research was to verify and determine the strength of the relationships of therapeutic alliance to well-being, life satisfaction, and flourishing in patients attending individual psychotherapy. The relationships were assessed based on different sources of information about the quality of the working alliance: patient’s evaluation and patient’s and psychotherapist’s joint evaluations. Design. The author applied Bordin’s pantheoretical model of alliance and two different conceptions of well-being, operationalized as hedonistic and eudaimonic. Methods. The 411 participants included 252 patients and 159 psychotherapists. To test the hypotheses, 16 joint and separate models of structural relations were built and analyzed empirically using SEM. Correlations were analyzed between alliance factors and those of well-being, satisfaction, and flourishing. Results. The actual impact of working alliance quality on psychological well-being proved to be stronger compared to the relations between alliance and satisfaction or flourishing. The results of analyses revealed low, though usually positive and significant, correlations between the dimensions of alliance and those of well-being, life satisfaction, and flourishing. Conclusions. The empirical data and the strategy of analyses brought the expected results, confirming that patient’s and psychotherapist’s perception of a strong therapeutic alliance is crucial for the optimization of patient’s functioning and well-being. It turns out that the therapeutic alliance is, above all, a factor of well-being understood more deeply than merely as current pleasure. The study also showed that no factor isolated from other components of alliance increased the quality of patient’s mental functioning more than others.